Scheduling of a pumped-storage hydro in the day-ahead market and in the secondary reserve market - Fernandes, Filipe (2021)
The increasing integration of wind power in the Portuguese energy market has been raising some challenges in terms of operation and planning of the generation portfolio and of power system management, with ancillary services playing a major role in system stability. A generation company (GENCO) aiming at maximizing its profits has to deal with bids to several available markets, among which are the Day-ahead Market (DAM) and the Secondary Reserve Market (SRM). This paper presents a scheduling solution of a price-maker GENCO whose portfolio comprises a pumped-storage hydro (PSH) unit with variable pumping capacity, acting simultaneously in the DAM and SRM. The results were obtained for four different scenarios, where the PSH may or may not possess variable pumping capacity and compares the PSH behavior in one or both markets simultaneously. The model was implemented in General Algebraic Modeling System (GAMS) as a Mixed Integer Programming (MIP) using CPLEX solver.